2009
DOI: 10.1063/1.3078032
|View full text |Cite
|
Sign up to set email alerts
|

Validating optical emission spectroscopy as a diagnostic of microwave activated CH4/Ar/H2 plasmas used for diamond chemical vapor deposition

Abstract: Spatially resolved optical emission spectroscopy ͑OES͒ has been used to investigate the gas phase chemistry and composition in a microwave activated CH 4 / Ar/ H 2 plasma operating at moderate power densities ͑ϳ30 W cm −3 ͒ and pressures ͑Յ175 Torr͒ during chemical vapor deposition of polycrystalline diamond. Several tracer species are monitored in order to gain information about the plasma. Relative concentrations of ground state H ͑n =1͒ atoms have been determined by actinometry, and the validity of this met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
141
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(164 citation statements)
references
References 29 publications
17
141
3
1
Order By: Relevance
“…The growth rate across the 100-mm wafer ranges from 2 µm/h for sample I up to 2.57 µm/h for sample H. Different parameters, like pressure, substrate temperature, methane percentage, hydrogen flow rate, etc., are known to affect the growth rate [41]. Axial and radial distributions of gas species and temperatures inside an MPCVD reactor were elaborately discussed by Ma in his thesis [42]; he showed that there is a wide variation in the species concentration and gas temperature away from the discharge core and the substrate. However, even though the hemispherical plasma symmetrically covers the whole 100-mmdiameter substrate surface, the temperature distribution is not radial.…”
Section: Growth Ratementioning
confidence: 99%
“…The growth rate across the 100-mm wafer ranges from 2 µm/h for sample I up to 2.57 µm/h for sample H. Different parameters, like pressure, substrate temperature, methane percentage, hydrogen flow rate, etc., are known to affect the growth rate [41]. Axial and radial distributions of gas species and temperatures inside an MPCVD reactor were elaborately discussed by Ma in his thesis [42]; he showed that there is a wide variation in the species concentration and gas temperature away from the discharge core and the substrate. However, even though the hemispherical plasma symmetrically covers the whole 100-mmdiameter substrate surface, the temperature distribution is not radial.…”
Section: Growth Ratementioning
confidence: 99%
“…[44][45][46] Figure 3 shows an image of the operating reactor, along with a schematic cross-section. MW radiation is delivered through a rectangular waveguide, converted to the TM01 mode and coupled into the cylindrical chamber.…”
Section: Microwave Activated Gas Mixtures For Diamond Cvdmentioning
confidence: 99%
“…Thus the emission intensities are intimately linked to the electron energy distribution function (EEDF), and can provide information about how the electron density (ne) and temperature (Te) vary with position and changes in process conditions. 45,60 High-resolution OES measurements can provide estimates of the temperature of the emitting species (through, for example, the Doppler broadening of lines in the Balmer series of atomic hydrogen or from the relative intensities of series of lines in the emission spectrum of H2 or of the C2 radical), which is often used as a proxy for the local Tgas. Actinometry, a variant of OES in which emission from a target species is measured in parallel with that from a small quantity of an inert tracer species (usually Ar), offers a route to determining the densities of, for example, ground state H atoms (a quantity that can be difficult to measure by laser based methods).…”
Section: Microwave Activated Gas Mixtures For Diamond Cvdmentioning
confidence: 99%
See 2 more Smart Citations